Corrigendum to the paper: “Spectacles of Shame: Ryan Murphy as Curator of Queer Cultural Memory” - Stepić, Nikola N. (Collection of Papers of the Faculty of Philosophy in Priština, 2017)
The author of this article would like to, with deepest apologies, issue a corrigendum regarding the usage of the term “hermaphrodite” (p. 80), a stigmatizing label that should have been replaced by the term “intersex” in the discussion of the character Desiree Dupree in American Horror Story: Freak Show. The misnomer was not meant pejoratively, and the author deeply regrets this error.